Rancang Bangun Aplikasi Sistem Informasi Bimbingan dan Konseling Berbasis Website dengan Menggunakan Framework Laravel di Sekolah Menengah Kejuruan Model Patriot IV Ciawigebang - Dijaya, Ramdan Ahmad; Nasrulloh, Sofhian Fazrin (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to design and develop a web-based Guidance and Counseling (BK) Information System Application using the Laravel framework at SMK Model Patriot IV Ciawigebang. The development method employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) using Laravel and Vite for backend development and asset management, the Atlantis 3.30 template based on Bootstrap 4 for a responsive interface, and MySQL as the database. Functionality testing by information systems experts showed a 100% suitability rating (highly suitable). Usability testing yielded a score of 83.9% (highly suitable) by guidance counselors, 54.3% (sufficiently suitable) by students, and 87.6% (highly suitable) by the student affairs department. These findings indicate that the application can improve the efficiency of BK administration, simplify online counseling services, accelerate the process of reporting student cases, and support the effectiveness of services through progress tracking modules, real-time notifications, and data security systems. Based on these results, the application is recommended for continued use in schools with regular maintenance and feature development according to user needs and feedback.